Evolution of Black-Box Models Based on Volterra Series - Daniel D. Silveira; Thiago V. N. Coelho; Alexandre Bessa dos Santos (Journal of Applied Mathematics)
This paper presents a historical review of the many behavioral models actually used to model radio frequency power amplifiers and a new classification of these behavioral models. It also discusses the evolution of these models, from a single polynomial to multirate Volterra models, presenting equations and estimation methods. New trends in RF power amplifier behavioral modeling are suggested.